PENGARUH INTELLECTUAL CAPITAL TERHADAP MARKET VALUATION SEKTOR PERBANKAN INDONESIA TAHUN 2004 – 2008 - Eliza, Eny (Universitas Islam Negeri Raden Intan Lampung, 2011)
Abstak: This research attempts to investigate empirically the impact of intellectual capital measured by value creation efficiency of intellectual capital and capital employed towards Market-to-Book Ratio (MBR). This research uses financial and capital market data of 120 banks listed on Indonesia Stock Exchange from 2004 to 2008. Empirical analysis is conducted using multiple linear regression. Findings from empirical analysis indicate that value creation efficiency of capital employed and structural capital have no impact on Market-to-Book Ratio; value creation efficiency of human capital has a negative impact on Market-to-Book Ratio. Key words: intellectual capital, MBR, bank, Indonesia Stock Exchange